2021
DOI: 10.1103/physrevb.103.245426
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confined Rydberg excitons in Cu2O nanoparticles

Abstract: The quantum confinement of Rydberg excitons is an important step towards exploiting their large nonlinearities for quantum applications. We observe Rydberg excitons in natural nanoparticles of Cu 2 O. We resolve up to the principal quantum number n = 12 in a bulk Cu 2 O crystal and up to n = 6 in nanoparticles extracted from the same crystal. The exciton transitions in nanoparticles are broadened and their oscillator strengths decrease as ∝n −4 compared to those in the bulk (decreasing as ∝n −3 ). We explain o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The constant is fitted to the particular geometry used in experiment. In the work [42], it has been shown that in Cu 2 O nanoparticles, the additional confinement potential produces a shift of the excitonic energy levels. Due to randomness of the particle size, the resulting shift is also random; the overlap of shifted lines produces one, wider linewidth.…”
Section: Rydberg Blockade Inclusionmentioning
confidence: 99%
“…The constant is fitted to the particular geometry used in experiment. In the work [42], it has been shown that in Cu 2 O nanoparticles, the additional confinement potential produces a shift of the excitonic energy levels. Due to randomness of the particle size, the resulting shift is also random; the overlap of shifted lines produces one, wider linewidth.…”
Section: Rydberg Blockade Inclusionmentioning
confidence: 99%
“…Deviation from this trend can be caused by confinement effects, whereby the wavefunction of a high energy exciton is comparable to the Cu 2 O film thickness [44]. The p-series exciton wavefunction size can be estimated as [6]…”
Section: Photoluminescence Measurementmentioning
confidence: 99%
“…(1) * jdelange@purdue.edu where E g is the bandgap energy, Ry is the binding energy, n is the principal quantum number of the state, and δ n is the quantum defect, which describes perturbations caused by the screening of Coulombic interactions within Cu 2 O's lattice and the non-parabolicity of Cu 2 O's band structure [4]. States with high principal quantum numbers, known as Rydberg states, are linked to long lifetimes which are proportional to n 3 , meaning that highly excited states could be used to obtain long coherence times on the order of nanoseconds [4,6]. Moreover, Rydberg excitons have wavefunction sizes which scale as n 2 , allowing them to interact via long-range dipole-dipole and Van der Waals interactions, which scale as n 4 and n 11 , respectively [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Rydberg excitons are becoming one of the most versatile, scalable and tunable platform for quantum computing technologies. The field is developing very rapidly, with first theoretical studies [17,18] and experiments [19,20] exploring nonlinear properties of RE in low-dimensional systems being performed right now. The fabrication techniques are just entering the stage where consistent synthesis of high-quality Cu 2 O nanostructures becomes possible [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…An exciton, being an excited electronic state of the crystal is an electron-hole air, which is weakly bound and can extend over many thousands of lattice unit cells, thus its interaction is screened by static permittivity of the semiconductor. The first observation of higher excited excitons, called Rydberg excitons, first in a cuprous oxide bulk [16] and then in nanostructures [19] revealed a lot of their astonishing features, such as extraordinary large dimension scaling as n 2 , long life-times ∼ n 3 , reaching nanoseconds. Their extraordinary vulnerability to interactions with external fields is due to huge polarizability scaling as n 7 .…”
Section: Introductionmentioning
confidence: 99%